2011
DOI: 10.1007/s10566-011-9150-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Parenting, Emotional Self-Efficacy, and Anxiety in Youth: Test of a Mediational Model

Abstract: Background Though associations between parenting styles marked by control (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 56 publications
3
36
4
2
Order By: Relevance
“…Unlike other studies that suggest that boys perceive higher control and rejection from their parents (Niditch & Varela, 2012), our results do not indicate gender differences in perception of parenting styles, but indicated grade level differences. 8 th graders perceived their parents as more authoritarian and more permissive than the 5 th and 7 th graders and less authoritative than 7 th graders.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other studies that suggest that boys perceive higher control and rejection from their parents (Niditch & Varela, 2012), our results do not indicate gender differences in perception of parenting styles, but indicated grade level differences. 8 th graders perceived their parents as more authoritarian and more permissive than the 5 th and 7 th graders and less authoritative than 7 th graders.…”
Section: Resultscontrasting
confidence: 99%
“…Niditch and Varela (2012) found that rejection from the mother predicts the increase of anxiety in adolescents, while mother control and father rejection and control do not have a significant effect.…”
Section: Parenting Style and School Anxietymentioning
confidence: 85%
“…Within this context, parents and teachers should do something to increase students' emotional self-efficacy levels, and create opportunity for students to support their development. In the literature, some studies indicate that perceived parental attitudes affect emotional self-efficacy and anxiety [34]. In this regard, supportive and democratic parental attitudes instead of rejectionist one, are important in terms of solving adolescent problems.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is a person's confidence in their own capabilities [39] which is strongly linked to how we feel [40]. Low levels of self-efficacy are often accompanied by high levels of anxiety [40][41][42]. In youth self-efficacy has been found…”
Section: The Role Of Self-efficacymentioning
confidence: 99%